The Challenge of Developing Entrepreneurial Competence in the University Using the Project-Oriented Learning Methodology - Crespí, Paula; Queiruga-Dios, Marián; Queiruga-Dios, Araceli (Frontiers in Psychology, 2022)
One of the objectives of the United Nations and the European Commission is to encourage the implementation of education plans and strategies to develop entrepreneurial competence. This refers to the ability to identify needs or discover opportunities and to act on them in order to create value for society. This paper aims to demonstrate the impact of the project-oriented learning (POL) methodology on the development of certain generic or transversal competences associated with entrepreneurship among first-year university students in Madrid. The competences associated with entrepreneurship analyzed in this work are: self-awareness, self-reliance, achievement orientation, proactivity, cooperative teamwork, team management, planning and organization by objectives and communication. The study used a single-group pre-test/post-test, quasi-experimental methodology with a sample of over 300 students of the Francisco de Vitoria University (UFV). The results show a significant increase in self-perceived development of transversal competences associated with entrepreneurship. These findings confirm the main hypothesis that POL is an ideal methodology for the development of transversal competences associated with entrepreneurship.